Price subsidies may impair competition in retail market for natural gas - Atabek Atayev; Adrian Hillenbrand (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
Policymakers have been discussing various potential measures to cushion the impact of skyrocketing gas prices and prevent supply shortages. On 10 October 2022 an expert commission in Germany proposed a plan to keep natural gas affordable while also preventing shortages. The main element of the plan is a direct subsidy for gas-consuming households. This ZEW Policy Brief aims to warn that price subsidies in the retail market for natural gas could impair competition between providers by reducing incentives for customers to search for cheaper service plans.
Keywords: 330